2012
DOI: 10.1038/mt.2012.39
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Correction of Very Long-chain Acyl-CoA Dehydrogenase Deficiency in Mice Using AAV9 Gene Therapy

Abstract: Very long-chain acyl-coA dehydrogenase (VLCAD) is the rate-limiting step in mitochondrial fatty acid oxidation. VLCAD-deficient mice and patients clinical symptoms stem from not only an energy deficiency but also long-chain metabolite accumulations. VLCAD-deficient mice were treated systemically with 1 × 1012 vector genomes of recombinant adeno-associated virus 9 (rAAV9)-VLCAD. Biochemical correction was observed in vector-treated mice beginning 2 weeks postinjection, as characterized by a significant drop in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 33 publications
(44 reference statements)
5
23
0
Order By: Relevance
“…The vector-specific primers used in PCR to detect rAAV DNA were CMV-F (5¢-CGTGTACGGTGGGAGGTCTATATAA-3¢) and CMV-R (5¢-GGATCGGTCCCGGTGTCT-3¢). For the quantification of rAAV vector DNA in rAAV-iPSC clones, quantitative real-time PCR (qPCR) was performed with vector-specific primers and a probe for CMV promoter sequences: forward primer, 5¢-CGTGTACGGTGGGAGGTC TATATAA-3¢; reverse primer, 5¢-GGATCGGTCCCGGTG TCT-3¢; and probe, 5¢-6FAM-ACGCCATCCACGCTGTTTT GACCT-TAMRA-3¢ (Keeler et al, 2012). In RT-PCR analysis, total RNA was purified with TRIzol reagent (Invitrogen).…”
Section: Pcr and Rt-pcrmentioning
confidence: 99%
“…The vector-specific primers used in PCR to detect rAAV DNA were CMV-F (5¢-CGTGTACGGTGGGAGGTCTATATAA-3¢) and CMV-R (5¢-GGATCGGTCCCGGTGTCT-3¢). For the quantification of rAAV vector DNA in rAAV-iPSC clones, quantitative real-time PCR (qPCR) was performed with vector-specific primers and a probe for CMV promoter sequences: forward primer, 5¢-CGTGTACGGTGGGAGGTC TATATAA-3¢; reverse primer, 5¢-GGATCGGTCCCGGTG TCT-3¢; and probe, 5¢-6FAM-ACGCCATCCACGCTGTTTT GACCT-TAMRA-3¢ (Keeler et al, 2012). In RT-PCR analysis, total RNA was purified with TRIzol reagent (Invitrogen).…”
Section: Pcr and Rt-pcrmentioning
confidence: 99%
“…In this study long-term expression of VLCAD protein, 147-182 days post injection, was observed in the liver and skeletal and cardiac muscle as well as brown fat (Keeler et al, 2012). Systemic correction was seen in reduction of blood acylcarnitine accumulation, but tissue-specific accumulation was measured in the liver and heart and muscle ex vivo and in the liver and muscle in vivo by MRS. Also for the first time disease-specific phenotypes of cold intolerance and coldinduced hypoglycemia and hypotonia were observed after correction, and animals receiving AAV9-expressing VLCAD behaved like wild-type animals (Keeler et al, 2012) (Fig. 3).…”
Section: Keeler and Flottementioning
confidence: 65%
“…[34] Moreover, blood profiles from animals and patients with VLCAD deficiency are characterized by large accumulations of long chain acyl carnitines. [35,36] …”
Section: Discussionmentioning
confidence: 99%